CLEAN WATER PIPELINE DESIGN OF A CITY AREA IN KALIMANTAN - An Nafi' Patragama, Tecta
One of the main needs in the development of a city area in Kalimantan is the provision of clean water that can be used during the construction process and can then be continued as the provision of clean water facilities for the community. During the construction process of a city area in Kalimantan, there will be around 70 thousand workers from various activity sectors who will work. Of course, clean water is needed to support development activities as well as the need for clean water for the above workers. This final project discusses the need for pumps and pipe systems to distribute clean water from the source of the clean water treatment plant to the ground water tank, which is about 2.8 kilometers long. The design of a clean water distribution pipe system is carried out by theoretical calculations or using software to determine pipe diameter, pump specifications, determine the maximum pressure that occurs in the pipe at steady or transient conditions, and analyze safety regarding the resistance of the pipe to the water hammer phenomenon. Based on the analysis carried out in this design, a piping system will be used to distribute clean water from the water treatment plant to the ground water tank using an 8 inch HDPE pipe with specifications SDR11 PE100 PN16 which is pumped through a Grundfos Hydro MPC-E 5 CRIE 20-7 pump with a power of 43.63 kW for 16 hours of operation and a Grundfos Hydro MPC-E 5 CRIE 15-4 pump with a power of 15.86 kW for 24 hours of operation. The pumps selected for both operational times do not experience cavitation. The maximum pressure for 16 hours of operation time is 7.22 bar at steady state and 10.38 bar at transient conditions. While the maximum pressure for 24 hours operating time is 4.52 bar at steady state and 6.71 bar at transient conditions. The water distribution pipe system is safe from the water hammer phenomenon at both operational times.